Identification and Characterization of Aeromonas spp. as a Specific Spoilage Organism in Chilled Storage of Rohu fish (Labeo rohita): Implications for Preservation Strategies - Joshi, Sagar A; Nayak, Binaya Bhusan; Balange, Amjad K; Kumar, Sanath H; Manjusha, L (Fishery Technology, 2025)
Rohu (Labeo rohita) is regarded as the most preferred carp in India. However, maintaining its freshness during transport is challenging. Chilling is commonly used for short-term preservation, but spoilage bacteria can remain active in ice, compromising fish quality. This study aims to identify specific spoilage bacteria (SSB) in rohu during 14-day period of chilled storage. The 16S rRNA sequencing of isolates from chilled rohu identified Aeromonas jandaei as the dominant bacterial species. Further, A. jandaei spiked rohu samples confirmed it as the SSB. The study findings highlight A. jandaei as SSB in chilled rohu, which can help processors in controlling its growth through better control of temperature, packaging, or use of preservatives.